Effect of ammonium administration on brain Na+-K+ATPase activity in mice - (:unkn) unknown (My University, 1990)
Ammonium acetate (7.8 mmol/kg body weight) was administered to mice intraperitoneally. Fifteen minutes after injection, the Na+-K+-ATPase activity of brain homogenates was found to be significantly decreased as compared to controls. This reduced activity was also observed at 30 and 60 minutes after ammonium acetate injection although progressive recovery in Na+-K+ATPase activity was observed at the later time points.